Debat Pilpres 2019 dalam Pikiran Generasi Millenial: Ajang Bertukar Ide, Tempat “Berkicau Galau”, atau Saluran Saling Sindir? - Rr Dinar Soelistyowati (Jurnal Ilmu Komunikasi AKRAB, 2019)
It cannot be avoided that communication is the most essential need in every aspectof human’s life. No matter what the field or where the activity is, it is human whose alwayscommunicate to express what they want, or at least, what they think. One of communicationfield which has increasement in its interraction level lately is politics, and the activity whombecome its trigger is the presidential debate. The purpose of this research is to give a pictureabout the reaction given from the millennial generation toward their social media based ontheir mind pattern, whether his position as an individual or a group’s member, with 2019Election Debate as a medium of informational exchange.This will discuss about the summaries about Election Debate results, millennialpublic’s judgement about a serial of its activities into their social media, either their positionas individuals or as the member of a social group and the implementation of their behaviorbased on their judgement. This research using the phenomenology theory as major theorysupported by the combination between technology determinism theory with transactionalanalysis theory as minor theories. The result from this research shows that the social mediaas digital comunication media has a powerful role and influence to the millennial public asone of vital element in giving the judgement to the presidential candidates’ vision, mission,and work program implementation which is served in the 2019 Election Debates.